Elevation of the provitamin A content of transgenic tomato plants - Römer, S.; Fraser, P.D.; Kiano, J.W.; Shipton, C.A.; Misawa, N.; Schuch, W.; Bramley, P.M.
Tomato products are the principal dietary sources of lycopene and major source of b-carotene, both of which have been shown to benefit human health. To enhance the carotenoid content and profile of tomato fruit, we have produced transgenic lines containing a bacterial carotenoid gene (crtI)encoding the enzyme phytoene desaturase, which converts phytoene into lycopene. Expression of this gene in transgenic tomatoes did not elevate total carotenoid levels. However, the b-carotene content increased about threefold, up to 45
Keywords: AGRICULTURAL BIOTECHNOLOGY; NUTRICEUTICALS; METABOLIC ENGINEERING